Klang und Wahrnehmung: Komponist, Interpret, Hörer - Institut für Neue Musik und Musikerziehung Darmstadt (Mainz Schott, 2001)
Until the 1970s, aesthetic theories were closely linked to musical thinking. Only recently has this relationship regained significance, stimulated by the desire to find aids to interpretation in a widely ramified musical culture. This volume reflects changing perceptions of art, new ideas of the artist-subject or possible and impossible symbolic contents of music. Shifts are beginning to become clear compared to the classical, work-orientated approach. More and more, aesthetics is returning to its original question of describing perception and experience in an aesthetic situation.
K. Zehelein: Luigi Nono -- G. Böhme: Akustische Atmosphären -- S. Sanio: Interaktion und Kommunikation in der ästhetischen Erfahrung -- W. Hopp: Vom Anteil der Sprache am musikalischen Hören -- H. G. Nicklaus: Pflanzen, Wunderkinder und Kastraten -- P. W. Schatt: Klang als Widerstand / Widerstand gegen Klänge: Aufgaben für den Musikunterricht -- H. Schneider: Kompositorisches Denken als Basis für musikpädagogische Tätigkeit -- S. Orgass: ... die alten Klänge hören, als seien sie nicht verbraucht ... -- O. Nimczik: Konstruktive Dekonstruktion -- B. Riede: Hörpartituren zu Luigi Nonos Werken mit Tonband -- M. Kontarsky: Lässt sich das Nichtverarbeitbare verarbeiten? -- J. M. Solare: Die ewige Utopie -- L. Jeschke: Nonos "Spätwerk"
Keywords: 20th Century (1901-2000); Music philosophy and esthetics